Pendugaan Potensi Karbon Jenis-Jenis Tanaman Berkayu di Pekarangan Desa Tegalwaru, Kecamatan Ciampea, Kabupaten Bogor - Nurheni Wijayanto; Maulana Musthofa Rasyiid Gunawan (Jurnal Silvikultur Tropika, 2020)
Global warming is an environmental issue that related to the forestry. The strategy to reduce greenhouse gases emissions can be done by mitigation and adaptation. Agroforestry is one of excellent step for mitigation. One example of agroforestry form is home garden. Home garden is a system of land use which is located around the home. This research aims to estimate total carbon stock potential in all of kinds of woody plants in home garden at Tegalwaru Village, Ciampea, Bogor. This research use allometric method. The study was conducted in 30 home gardens of Tegalwaru Village selected by randomly. The results showed that there were 31 species of woody plants. Plants that dominate, namely: rambutans (Nephelium lappaceum), rose apple (Syzygium aqueum), mango (Mangifera indica), and jackfruit (Artocarpus heterophyllus). The total amount of biomass and carbon stocks for woody plants there is 14.98 ton ha-1 and 7.04 ton ha-1. Carbon stocks in woody plants at home garden of Tegalwaru Village is low carbon stocks. Keywords: allometric, carbon potential, home garden, Tegalwaru Village, woody plants